(untitled) (International Journal of Food and Nutritional Sciences, 2019)
The business environment is changing due to artificial intelligence, which presents HRM with both possibilities and problems. Whether an organisation choose to go forward or stagnate relies on its ability to overcome its outdated management style and successfully execute digital transformation.